2004
DOI: 10.1021/bi030266t
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electric Charge Variation at Residues 209 and 159 on the Interaction of eIF4E with the mRNA 5‘ Terminus

Abstract: Eukaryotic translation initiation factor 4E (eIF4E) is essential for efficient protein synthesis in cap-dependent translation. The protein specifically binds the cap structure at the mRNA 5' terminus and facilitates the assembly of the mRNA with other initiation factors and the 40S ribosomal subunit. Phosphorylation of eIF4E is implicated in the regulation of the initiation step of translation. However, the molecular mechanism of this regulation still remains unclear. To address this problem, we have determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
76
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(84 citation statements)
references
References 33 publications
8
76
0
Order By: Relevance
“…In the absence of any difference in cellular vRNA and mRNA, the mechanism for altered amounts of HA protein is likely to act posttranscriptionally, altering viral protein translation. Upon influenza virus infection, the cellular translation initiation factor eIF4E, which recognizes the cap of mRNA, may become dephosphorylated and so host-cellular cap-dependent translation is inhibited (33)(34)(35)(36). Nevertheless, translation of the capped viral mRNA still occurs independently of eIF4E (37), and recently, it has been shown that the viral polymerase complex can act as a substitute for eIF4E (25).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of any difference in cellular vRNA and mRNA, the mechanism for altered amounts of HA protein is likely to act posttranscriptionally, altering viral protein translation. Upon influenza virus infection, the cellular translation initiation factor eIF4E, which recognizes the cap of mRNA, may become dephosphorylated and so host-cellular cap-dependent translation is inhibited (33)(34)(35)(36). Nevertheless, translation of the capped viral mRNA still occurs independently of eIF4E (37), and recently, it has been shown that the viral polymerase complex can act as a substitute for eIF4E (25).…”
Section: Discussionmentioning
confidence: 99%
“…Cap analogues, mutants of eIF4E, fluorescence titration measurements and experimental data Synthesis of cap analogues, mutagenesis, expression and purification of eIF4Es, as well as fluorescence measurements and data analysis were described in detail elsewhere [24].…”
Section: 1mentioning
confidence: 99%
“…The standard Gibbs free energy changes for complex formation were calculated from the K ass values according to the standard equation ∆G o = −RTlnK ass . The presented equilibrium binding constants for complexes of wild type and mutated eIF4E protein with m 7 GTP ligand were determined for the purpose of the present work, the remaining equilibrium binding constants connected to m 7 Gp 4 ligand were reported previously [24].…”
Section: 1mentioning
confidence: 99%
See 2 more Smart Citations